THE SIMILARITIES BETWEEN ASTON’S THE SECOND MRS. DARCY AND AUSTEN’S PRIDE AND PREJUDICE - Susie Chrismalia Garnida; Aulia Qanita Amini (Universitas 17 Agustus 1945 Surabaya, 2023)
In reading texts, whether literary works or non-literary works, the readers may find similarity between one text and other texts. This similarity creates a connection which is called intertextuality. Fairclough (1989) stated that intertextuality is a part of interpretation of a text based on Critical Discourse Analysis. There are three stages of Critical Discourse Analysis: description, interpretation, and explanation. This article is about an intertextuality between Elizabeth Aston’s The Second Mrs. Darcy and Jane Austen’s Pride and Prejudice. The focus of this study is to find and classify the similarity between two novels, interpret and explain the intertextual similarities between them. The findings show that there are 4 intertextual features which can be found in the data; introductory sentence, characters, settings, and plots. These show that Elizabeth Aston’s The Second Mrs. Darcy has several similarities which connect to Jane Austen’s Pride and Prejudice. The possible motifs of Elizabeth Aston in building intertextuality links between her The Second Mrs. Darcy and Jane Austen’s Pride and Prejudice are (1) to create continuity of Jane Austen’s Pride and Prejudice, (2) to show her expertise in writing is as great as Jane Austen, (3) to create or re-write the existing idea by developing different or new focus